EDUCATIONAL SOFTWARE DEVELOPMENT FOR DESING OF STEEL STRUCTURES LESSON - Yilmaz, Orkun; Sahin, Abdurrahman (YILDIZ TECHNICAL UNIV, 2013)
In this paper, new educational software developed for Design of Steel Structures lesson is presented. The software is named as STR2 and developed by using MATLAB which is a mathematical tool. All design steps can be monitored by using the software. To analyze the structure, the user do not assign loads to joints and elements, self-load of system, snow load and wind load are assigned to system automatically. Finite Element Method is used for structural analysis. The structural system can be designed according to TS648.
Keywords: Finite element method; educational software; design of steel structures; Engineering